DeLone Model Assessment and McLean Information Success System Over Esa Unggul University Website - Irawati Irawati; Tantri Yanuar Rahmat Syah (Penerbit Kemala Indonesia, 2020)
User satisfaction is the impact of a good information system. Here, user satisfaction can be influenced by several factors such as system quality, information quality, and user intensity. Thus, in this study aims to test and provide the empirical evidence also analyze the effect of system information quality and user intensity at user satisfaction. Here, we used a SEM model and used AMOS 23 to obtain the results. The result shows system quality has no effect on user intensity while information quality affects user intensity. Here, user intensity has no effect on user satisfaction due to system quality has no effect on user satisfaction. In addition, information quality has no effect on user satisfaction.